IDENTIFIKASI SPORA JAMUR MIKORIZA VESIKULAR ARBUSKULAR (MVA) PADA TANAH TERCEMAR MINYAK BUMI DI BOJONEGORO - FAIZA, RIZKA (Universitas Negeri Surabaya, 2013)
Exploration of oil cause an oil spill or pipeline leak on a large scale, which causes contamination of land in the area. To recover petroleum contaminated land require as microbial endemic like mycorrhizal as an alternative. The objective of this research were to explore, identify and determine the density of spores of mycorrhizal of petroleum contaminated soil, besides identifying infected mycorrhizal plants. Soil samples were obtained as composite sampling during identifying and trapping of mycorrhyza. The result obtained 7 types of spore of mycorrhyza namely Glomus sp. (2 types), Gigaspora sp. (3 types), Acaulospora sp. (1 type) and Sclerocystis sp. (1 type). Plants that had symbiosis with micorrhyza were Stachytarpheta mutabilis, Lantana camara L, Imperata cylindrica L, Calotropis gigantea, Eupatorium odoratum L, Sida rhombifolia L and Tectona grandis L. The highest spore density on soil that is covered by plants Sida rhombifolia was 61 spore/50 g soil.